2019
DOI: 10.3847/1538-4357/ab16d1
|View full text |Cite
|
Sign up to set email alerts
|

Electron Preacceleration in Weak Quasi-perpendicular Shocks in High-beta Intracluster Medium

Abstract: Giant radio relics in the outskirts of galaxy clusters are known to be lit up by the relativistic electrons produced via diffusive shock acceleration (DSA) in shocks with low sonic Mach numbers, M s 3. The particle acceleration at these collisionless shocks critically depends on the kinetic plasma processes that govern the injection to DSA. Here, we study the preacceleration of suprathermal electrons in weak, quasi-perpendicular (Q ⊥ ) shocks in the hot, high-β (β = P gas /P B ) intracluster medium (ICM) throu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
68
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 62 publications
(72 citation statements)
references
References 58 publications
2
68
0
Order By: Relevance
“…The electron preacceleration has been a key outstanding problem in understanding the production of CR electrons in weak ICM shocks. Previous studies have shown that, in low-M s , high-β Q ⊥ shocks, thermal electrons could be preaccelerated primarily through the Fermi-like acceleration in the shock foot (Matsukiyo et al 2011;Guo et al 2014aGuo et al , 2014bKang et al 2019) and the stochastic shock drift acceleration (SSDA) in the shock transition region (Katou & Amano 2019;Niemiec et al 2019;. Although it has been shown that the electron preacceleration would be enhanced by preexisting strong magnetic fluctuations in the low-β (∼1) regime (e.g., Guo & Giacalone 2015;Trotta et al 2020), the effect of such turbulence on high-β ICM shocks has yet to be investigated and will not be considered here.…”
Section: Introductionmentioning
confidence: 99%
“…The electron preacceleration has been a key outstanding problem in understanding the production of CR electrons in weak ICM shocks. Previous studies have shown that, in low-M s , high-β Q ⊥ shocks, thermal electrons could be preaccelerated primarily through the Fermi-like acceleration in the shock foot (Matsukiyo et al 2011;Guo et al 2014aGuo et al , 2014bKang et al 2019) and the stochastic shock drift acceleration (SSDA) in the shock transition region (Katou & Amano 2019;Niemiec et al 2019;. Although it has been shown that the electron preacceleration would be enhanced by preexisting strong magnetic fluctuations in the low-β (∼1) regime (e.g., Guo & Giacalone 2015;Trotta et al 2020), the effect of such turbulence on high-β ICM shocks has yet to be investigated and will not be considered here.…”
Section: Introductionmentioning
confidence: 99%
“…In effect, electron spectra are formed in a wideenergy range, and the maximum Lorentz factor reaches γ max ≈ 60. This value is much larger than is needed for injection to DSA, γ inj ≈ 25, estimated under assumption that the injection momentum p inj ∼ 3p th,i [6]. The fraction of supra-thermal particles reaches 5%, and ∼ 40% of the energy…”
Section: Pos(icrc2019)368mentioning
confidence: 93%
“…Total plasma beta β = 5 (β e = β i = 2.5). Although this value is lower than β assumed in simulations in which EFI is strongly excited [4,6], it is a necessary compromise to fit the ion-scale rippling modes in the simulation box and at the same time allow to follow the long-time development of the system under available computing resources. We apply a reduced ion-to-electron mass ratio m i /m e = 100.…”
Section: O ) With the Magnetic Field A Motional Electric Fieldmentioning
confidence: 96%
See 2 more Smart Citations